Successful replantation of an amputated helical rim with microvascular anastomosis - Seo, Bommie Florence (Arch Craniofac Surg, 2018)
Replantation using microvascular anastomosis is considered to be the optimal method in treating the amputated ear in terms of resulting color, texture, and shape. Only a few cases of ear replantation have been reported because it is anatomically difficult to identify suitable vessels for anastomosis. We successfully replanted the amputated helical rim of the ear using single arterial anastomosis. A 37-year-old man had his helical rim amputated by a human bite. The amputee was about 4 × 1 cm in dimension, composed of skin and soft tissue including auricular cartilage. Replantation was performed anastomosing a small artery of the amputee with a terminal branch of the posterior auricular artery. After replantation, intravenous heparinization was performed and prostaglandin E1 and aspirin were administered. Venous congestion was decompressed by stab incisions applied with heparin solution soaked gauze. Venous congestion of the amputee slowly began to resolve at 4 days after the operation. The amputated segment of the helical rim survived completely with good aesthetic shape and color. The authors propose that performing microvascular anastomosis should be attempted especially if it is possible to detect vessels on cut surfaces of ear amputee and stump. Proper postoperative care for venous congestion, arterial insufficiency, and infection should be followed for amputee survival.